Performance of microscopy and RDTs in the context of a malaria prevalence survey in Angola: a comparison using PCR as the gold standard - Fançony, Cláudia (BioMed Central, 2013)
BACKGROUND: Accurate identification of Plasmodium infections in community surveys is essential to successful malaria control. Microscopy and rapid diagnostic tests (RDTs) are the main techniques used to diagnose malaria in field-based surveys. While microscopy is still considered the gold standard, RDTs are growing in popularity as they allow for rapid and inexpensive diagnosis. Using data from a prevalence survey conducted in north-western Angola in 2010, the authors aimed to compare the performance of microscopy and RDTs in identifying Plasmodium falciparum infections, using polymerase chain reaction (PCR) as the gold standard. METHODS: Results from 3,307 subjects (1,225 preschool-aged children (zero to five year olds), 1,134 school-aged children (six to 15 year olds) and 948 mothers/caregivers (>15 years of age)), tested for P. falciparum infections, were utilized. The sensitivity, specificity, positive, and negative predictive values (PPV and NPV) of microscopy and Paracheck-Pf(®) were compared using the McNemar’s test and the weighted generalized score Chi-squared test for paired data. RESULTS: The prevalence of P. falciparum infections determined by PCR and microscopy was 15.9% and by Paracheck- Pf(®) was 16.3%. Compared to microscopy, Paracheck-Pf(®) had significantly higher sensitivity (72.8% versus 60%), specificity (94.3% versus 92.5%), PPV (70.7% versus 60%) and NPV (94.8% versus 92.5%). Both tests had significantly lower sensitivity in mothers (36.8% for microscopy and 43.7% for Paracheck-Pf(®)) than in their children (68.4% in zero to five years-old and 60.6% in six to 15 years-old for microscopy and 80.4% in zero to five year-olds and 76.5% in six to 15 year-olds for Paracheck-Pf(®)). CONCLUSION: Both microscopy and RDTs performed suboptimally when compared to PCR. False negativity could be associated with the low parasite density profile of the samples. False positivity may be related to the well-described limitations of those techniques such as level of expertise of microscopists or persistent antigenicity from previous infections in the case of RDTs. Nevertheless, RDTs had enhanced performance comparatively to microscopy in detecting malaria infections, favouring their use in community cross-sectional malaria surveys, where expert performance of microscopy is hard to accomplish.